Dual ECM Biomimetic Scaffolds for Dental Pulp Regenerative Applications - Huang, Chun-Chieh; Narayanan, Raghuvaran; Warshawsky, Noah; Ravindran, Sriram (Frontiers in Physiology, 2018)
Dental pulp is a highly vascularized and innervated tissue that provides sensitivity and vitality to the tooth. Chronic caries results in an infected pulp tissue prone to necrosis. Existing clinical treatments replace the living pulp tissue with a non-responsive resin filling resulting in loss of tooth vitality. Tissue engineering approaches to dental pulp tissue regeneration have been investigated to preserve tooth vitality and function. However, a critical criterion is the choice of growth factors that may promote mesenchymal stem cell differentiation and more importantly, vascularization. But, the problems associated with growth factor dosage, delivery, safety, immunological and ectopic complications affect their translatory potential severely. The purpose of this study is to develop, characterize and evaluate a biomimetic native extracellular matrix (ECM) derived dual ECM scaffold that consists of a pulp-specific ECM to promote MSC attachment, proliferation and differentiation and an endothelial ECM to promote migration of host endothelial cells and eventual vascularization in vivo. Our results show that the dual ECM scaffolds possess similar properties as a pulp-ECM scaffold to promote MSC attachment and odontogenic differentiation in vitro. Additionally, when implanted subcutaneously in a tooth root slice model in vivo, the dual ECM scaffolds promoted robust odontogenic differentiation of both dental pulp and bone marrow derived MSCs and also extensive vascularization when compared to respective controls. These scaffolds are mass producible for clinical use and hence have the potential to replace root canal therapy as a treatment for chronic dental caries.